2016
DOI: 10.1044/2015_lshss-15-0051
|View full text |Cite
|
Sign up to set email alerts
|

Using Language Sample Analysis to Assess Spoken Language Production in Adolescents

Abstract: Language sample analysis remains a powerful method of documenting language use in everyday speaking situations. A sample of talking reveals an individual's ability to meet specific speaking demands. These demands vary across contexts, and speakers can have difficulty in any one or all of these communication tasks. Language use for spoken communication is a foundation for literacy attainment and contributes to success in navigating relationships for school, work, and community participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
109
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 17 publications
1
109
0
8
Order By: Relevance
“…The language produced by the participant and the examiner or parent was transcribed from digital video using Systematic Analysis of Language Transcripts software (SALT; Miller, Andriacchi, & Nockerts, 2011). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The language produced by the participant and the examiner or parent was transcribed from digital video using Systematic Analysis of Language Transcripts software (SALT; Miller, Andriacchi, & Nockerts, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Utterances were segmented using phonological units (P-units; Miller et al, 2011). Segmenting utterances based upon P-units documents thought completion based on falling or rising intonation and pauses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first three minutes were excluded to allow the child to get comfortable in the play activity. An analysis of 50 utterances is considered valid for measuring the morphosyntactic skills of young children (Logan, Piasta, Justice, Schatschneider, & Petrill, 2011;Miller et al, 2016;Paul & Norbury 2012). If the recording did not include 50 utterances starting from the third minute of play, the transcription was started earlier and continued until a sample of 50 utterances was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Number of different words (NDW) was calculated from the transcripts as a measure of child vocabulary and an indicator of lexical diversity (Miller, Adriacchi, & Nockerts, 2011). All of the children in the present study were identified via parent report as monolingual Spanish speakers.…”
Section: Methodsmentioning
confidence: 99%